2013
DOI: 10.1089/ten.tea.2012.0673
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic Potential of Articular Chondrocytes Depends on Their Original Location

Abstract: Objective: This study aimed to investigate the regenerative capacity of chondrocytes derived from debrided defect cartilage and healthy cartilage from different regions in the joint to determine the best cell source for regenerative cartilage therapies. Methods: Articular cartilage was obtained from Outerbridge grade III and IV cartilage lesions and from macroscopically healthy weight-bearing and nonweight-bearing (NWB) locations in the knee. Chondrocytes isolated from all locations were either pelleted direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Improved cell yields were observed for articular cartilage with a cell yield of 2-2.5 x 10 6 cells/g from a clinically relevant biopsy (~300 mg) (17) using a reduced isolation time of 30 min. This is comparable to previous work by Bekkers et al who report similar cell yields 0.56-1.06 x 10 6 cells/g (26). Exposure time was found to be more detrimental to cell viability than concentration as previously demonstrated by Bos et al (46).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Improved cell yields were observed for articular cartilage with a cell yield of 2-2.5 x 10 6 cells/g from a clinically relevant biopsy (~300 mg) (17) using a reduced isolation time of 30 min. This is comparable to previous work by Bekkers et al who report similar cell yields 0.56-1.06 x 10 6 cells/g (26). Exposure time was found to be more detrimental to cell viability than concentration as previously demonstrated by Bos et al (46).…”
Section: Discussionsupporting
confidence: 91%
“…In this manner, the application of fresh chondrocyte based biologics demonstrates the Where the use of enzymatic isolation protocols intraoperatively is largely reliant on the evolving regulatory landscapes, the efficacy of tissue transplantation with minced cartilage without the need for enzymatic cell isolation has been demonstrated in cartilage approaches (26,29). However, to the best of the authors' knowledge, the application of such has not been applied to meniscal replacement procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of post-mortem collection of healthy synovial fluid and cells as opposed to the intra-operative collection of OA and cartilage defect synovial fluid and cells is less likely to have affected the results. Previous work from our group showed that there was no difference in viability between freshly isolated chondrocytes from healthy (post-mortem obtained) and grade III cartilage defect tissue [49], which is in line with the observation that viability and cartilage matrix content is very much unaltered within the first 24 hours [74-76]. Synovial fluid is contained in a relatively isolated compartment [77,78] and when kept at 4°C, levels of IL-6 have been shown to be stable for more than six hours [79].…”
Section: Discussionmentioning
confidence: 99%
“…The debrided cartilage was used for chondrocyte isolation. Chondrocytes from this location were recently shown to have good regenerative capacities compared to cells harvested from non-weight bearing cartilage normally used for ACI [49]. Of the 22 patients with symptomatic cartilage defects, one had an associated ACL injury and a history of partial menisectomy, another three had previously received partial menisectomies and one had undergone an ACL reconstruction.…”
Section: Methodsmentioning
confidence: 99%